The consequences of external factors of smoking behaviour on the risk of dental caries among teenage smokers and non-smokers at SMKN 2 Padang: Konsekuensi faktor eksternal perilaku merokok pada risiko karies remaja perokok dan non perokok di SMKN 2 Padang - Adriani, Sabrina Arifah; Rahmad, Yulia; Fadriyanti, Okmes (Makassar Dental Journal, 2025)
Smoking behaviour among adolescents has become one of the main factors affecting dental and oral health, particularly in in-creasing the risk of caries. Data from Health Office of Padang City shows a high prevalence of dental caries at SMKN 2 Padang. This article reports the results of a study on the consequences of external factors of smoking behaviour on the risk of dental caries among adolescent smokers and non-smokers at SMKN 2 Padang. A quantitative cross-sectional study was conducted with 68 Grade XI students at SMKN 2 Padang. Data were collected through oral cavity examinations using the DMF-T index and ques-tionnaires evaluating external factors such as the influence of parents, peers, and cigarette advertisements. Univariate data ana-lysis was presented in tables, and bivariate analysis was performed using the Mann-Whitney test. It was found that smoking stu-dents had a higher severity of caries compared to non-smoking students. A total of 13 students (19.12%) who smoked had very high levels of caries, while 34 non-smoking students had a caries level of 0. It was concluded that dental caries in smokers was higher and the main cause was peer influence.